Dana Syirkah Temporer Dan Corporate Governance Mechanism Mempengaruhi Kinerja Maqasid Syariah Bank Syariah Di Indonesia - Z. Zulpahmi; S. Sumardi; A. Andika (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
This study aims to determine the effect of temporary syirkah funds, the size of the board of commissioners, board meeting, size of the board of directors, a board of directors meeting, the size of the sharia supervisory board, sharia supervisory board meetings, and sharia maqasid performance in Islamic banking in Indonesia. In this study explanatory methods are used. The variables studied were temporary syirkah fund, board size, a board of commissioners meeting, board size, a board of directors meeting, size of sharia supervisory board, meeting of sharia supervisory board as independent variables and sharia maqasid performance as dependent variables. The population in this study is a Sharia Commercial Bank (BUS). Sample selection technique used judgment sampling and obtained a sample of 6 (six) Islamic banking. Data collection techniques used are document review, namely Islamic banking financial statements. Processing techniques and data analysis used are multiple linear regression analysis, classical assumption test, hypothesis testing, and analysis of the coefficient of determination.